Strategies for teaching confusing topics in Mathematics: A case study - Faye, I. (2013)
Some topics in Mathematics can be confusing for students. Given two very close topics in Mathematics, how should they be taught? Will it better to teach them back to back or will it be better to insert some other topics in between. This paper considers the use of Power Series and Fourier series in solving Differential Equations. Two groups of students were taught the two topics. The first group has the two topics taught back-to-back while the second had one topic (Laplace transform) inserted between the two. The two groups were then assessed with a set of questions combining Power Series and Fourier series. The results showed that the mean of the group that had Power and Fourier series back-to-back is higher compared to the mean for the group that had the insertion of Laplace transform between Power series and Fourier series. The difference is statistically significant as showed through a T-tests. Â© 2013 IEEE.